Self-esteem and values in microenterprises of east zone of Lima - Loli Pineda, Alejandro (1999)
It was investigated on the values hierarchy that prevails in the small business of the east zone of Lima, the relationship between self-esteem and the organizational values. and the differences between the self-esteem and some demographic features, as well as these with the organizational values. The study was carried out in a sample of 105 managers of equal number o small business. The information was collected through the Inventory of self-esteem (ALPEL) VA-Form. and the Values Organizational List (ALPEL) VA-Form. The analysis of the results indicate us that indeed exists a hierarchy of values. even though of very little importance, but of the most elected. Equally, it exists positive correlation and moderated other high self-esteem with loyalty and love to the work, and a negative correlation of the low self-esteem with loyalty and the work in team. On the other side, the correlation between self-esteem and so me organizational values with demographic features there are more differences.